Potential TRIP/TWIP coupled effects in equiatomic CrCoNi medium-entropy alloy. (1st August 2022) - Ding, L.; Hilhorst, A.; Idrissi, H.; Jacques, P.J.
Abstract: High-entropy alloys (HEA) and medium-entropy alloys (MEA), containing multiple principal elements typically with equiatomic or near-equiatomic ratios, have drawn considerable attention due to their unique and promising mechanical profiles, such as high tensile strength, superior ductility and exceptional fracture toughness. However, the elementary mechanisms controlling the deformation and fracture of this new class of alloys still need complementary analyses. In the present study, the nucleation and growth mechanisms of deformation bands in the medium-entropy CrCoNi alloy were investigated by atomic-resolution scanning transmission electron microscopy (STEM). It was revealed that planar dislocation slip is the dominant deformation mode in the early stages of deformation. With increasing strain, both deformation twins and hexagonal close packed (HCP) lamella simultaneously appear. Careful analysis of the dislocations involved in these processes confirms that two different mechanisms are responsible for the nucleation of deformation bands in the CrCoNi alloy: the three-layer mechanism proposed by Mahajan et al. and the transformation from HCP phase to twin. Activation of multiple slip systems at larger deformation levels leads to the activation of deviation-based mechanisms, which contribute to the twin growth. It was also observed that many HCP bands remain and overlap with nanoscale twins, leading to short range HCP-twin stackings, which contribute to the high work hardening rate of this alloy. Graphical abstract: Image, graphical abstract